2018
DOI: 10.1016/j.jpeds.2018.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Home Matters: Adolescents Drink More Sugar-Sweetened Beverages When Available at Home

Abstract: Objectives To examine the association between sugar-sweetened beverage availability at home and sugar-sweetened beverage consumption, and to evaluate whether this association was consistent across school and school neighborhood sugar-sweetened beverage availability. Study design Secondary data analyses were performed from the 2014 cross-sectional, Internet-based Family Life, Activity, Sun, Health, and Eating (FLASHE) study of 1494 adolescents (age 12–17 years). Ordinal logistic regression analyses were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
(40 reference statements)
5
21
0
1
Order By: Relevance
“…While the intervention was not significantly associated with parental SSB purchasing or SSB availability at home, within-group analyses indicated intervention site parents were less likely to report availability of SSBs at home at 2 and 6 months. This finding is important given our prior research demonstrating that availability of SSBs at home is a strong predictor of youth SSB consumption, regardless of SSB availability in the school or neighborhood settings [76]. Overall, our pilot study results demonstrate the potential of engaging youth and parents to support decreased SSB consumption and increased water consumption through a community-based youth empowerment intervention.…”
Section: Discussionsupporting
confidence: 54%
“…While the intervention was not significantly associated with parental SSB purchasing or SSB availability at home, within-group analyses indicated intervention site parents were less likely to report availability of SSBs at home at 2 and 6 months. This finding is important given our prior research demonstrating that availability of SSBs at home is a strong predictor of youth SSB consumption, regardless of SSB availability in the school or neighborhood settings [76]. Overall, our pilot study results demonstrate the potential of engaging youth and parents to support decreased SSB consumption and increased water consumption through a community-based youth empowerment intervention.…”
Section: Discussionsupporting
confidence: 54%
“…party, holidays). Previous studies had already identified the availability of SSB at home (28,48,(57)(58)(59) and school (60) ; having parents (48,58,59,61) and friends (58,62) who consume SSB; the taste of SSB (54) and eating at fast-food restaurants (58) as correlates of SSB consumption among adolescents. The two facilitating factors were an easy access to water (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents seem to be the major consumers of SSBs, in which SSBs have become the major contributor of energy intake in their diet [4]. The Internet-based Family Life, Activity, Sun, Health, and Eating (FLASHE) study reported that 67.4% of adolescents (12–17 years old) in the United States consumed SSBs on a daily basis, 33.9% took between one and less than two SSBs, and 33.5% consumed two or more SSBs daily [9]. Likewise, the Ontario Student Drug Use and Health Survey revealed that 81.4 and 12.0% of middle- and high-school students (11–20 years old) consumed at least one SSB and energy drink during the preceding week, respectively [10].…”
Section: Introductionmentioning
confidence: 99%